Pengaruh Fasilitas Belajar, Persepsi Profesi Guru dan Minat Menjadi Guru Terhadap Kesiapan Menjadi Guru (Studi Mahasiswa Pendidikan Ekonomi Universitas Negeri Padang) - Crisma Yanti; Syamwil Syamwil (Jurnal Salingka Nagari, 2022)
This type of research is a type of survey research; survey research is research by providing clear boundaries about the data. The data used are primary data. Data collection techniques are in the form of test and no test questionnaires. Data analysis used descriptive analysis. The place and time of the research were carried out at the Faculty of Economics, UNP with a population of 155, analysis requirements test, multiple regression, F test, determinant of learning facilities, teacher’s professional. The results of the study show that 1) The Effect of Learning Facilities, Perceptions of Teacher Profession and Interests in Becoming a Teacher Together on Readiness to Become a Teacher can be seen from the significance. 2) Learning facilities on readiness to become teachers in Economic Education students, Padang State University. 3) the perception of the teaching profession as a teacher on the readiness to become a teacher in Economic Education students at the Padang State University. 4) interest in becoming a teacher towards the readiness to become a teacher at Padang State University Economic Education students